Happiness at Work: Organizational Values and Person-Organization Fit Impact - Sousa, Juliana Moraes de; Porto, Juliana Barreiros (Paidéia (Ribeirão Preto), 2015)
Despite the large quantity of research on person-organization (PO) fit, there is a lack of empirical research using axiological theories applicable to the value structure at the individual and organizational levels. In this study, we incorporated the PO fit literature, Schwartz’ values theory and Warr’s vitamin analogy to evaluate the effect of values’ PO fit on happiness at work. Using a sample of 145 questionnaires collected in a military organization, data analyses were performed using hierarchical quadratic regressions and surface analysis of polynomial regressions, conducted at an individual level. Individual values moderated the curvilinear relationship between organizational values and happiness at work (R2 = .25; p < .01). Additionally, agreement between higher levels of values promoted higher levels of happiness at work (.07 ≥ R2 ≤ .18; p < .05). We concluded that axiological PO fit affects happiness at work and provide empirical support for Warr’s vitamin analogy.